Morphometric and morphological analysis of neuromuscular junction alterations in the denervated rat diaphragm - Torrejais, M. M. (2009)
The morphological and structural alterations that occur in the neuromuscular junctions of the denervated rat diaphragm were studied. Fifteen adult male albino rats (Rattus norvegicus) aged about 60 days and with a mean weight of 200 g were used. Chronically denervated diaphragms were obtained and the animals were sacrificed after 4, 8 and 12 weeks of denervation. The left antimere of the diaphragm was denervated by section of the phrenic nerve and the right antimere was used as control. Each antimere was divided into three fragments: one was used for histochemical (nonspecific esterase) and morphometric study of neuromuscular junctions, and the other two were used for transmission and scanning electron microscopy (SEM) analysis. Histochemical analysis of the diaphragm neuromuscular junctions after denervation showed only small changes in junction morphology. However, these junctions became smaller and elongated and presented less visible contours with increasing time of denervation. Ultrastructural analysis of neuromuscular junctions after 12 weeks showed more or less organized junctional folds on the muscle fiber surface. The junctional cytoplasm exhibited important alterations such as mitochondrial degeneration and the presence of numerous filaments. SEM revealed the presence of deep primary synaptic grooves with peripheral excavations which housed the nerve terminal boutons and exhibited internally the secondary synaptic clefts present among the junctional folds of the sarcolemma. This study showed that some of the morphological changes demonstrated in other denervated striated skeletal muscles are not repeated at the same intensity or in the same temporal pattern in the rat diaphragm.